The Synergy of Financial Sector Development and Information Sharing in Financial Access: Propositions and Empirical Evidence - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
This study assesses the role of information sharing in financialization (or coexistence of financial sub-systems) for financial access. The empirical evidence is based on contemporary and non-contemporary Fixed Effects and Quantile regressions on 53 African countries for the period 2004-2011. The positive complementarity of information sharing offices (ISOs) and financial formalization is an increasing function of financial activity (or access to credit) whereas the negative complementarity of ISOs and financial informalization is a decreasing function of financial activity. In order to leverage on the synergy between ISO and financial formalization for enhanced financial access, some policy measures are proposed.
Keywords: G20; G29; L96; O40; O55; 330; Information Asymmetry; Financialization; Financial Access